2014
DOI: 10.1093/mnras/stu969
|View full text |Cite
|
Sign up to set email alerts
|

Search for X-ray occultations in active galactic nuclei

Abstract: Recent time-resolved spectral studies of a few Active Galactic Nuclei in hard X-rays revealed occultations of the X-ray primary source probably by Broad Line Region (BLR) clouds. An important open question on the structure of the circumnuclear medium of AGN is whether this phenomenon is common, i.e. whether a significant fraction of the X-ray absorption in AGN is due to BLR clouds. Here we present the first attempt to perform this kind of analysis in a homogeneous way, on a statistically representative sample … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…X-ray photoelectric absorption variability has also been found in many Seyfert 2s (e.g., Risaliti et al 2002Risaliti et al , 2007. Modeling of the observed absorption variations suggests this absorption originates in gas clouds in the BLR or torus orbiting the central source (e.g., Maiolino et al 2010;Markowitz et al 2014;Torricelli-Ciamponi et al 2014;Netzer 2015). X-ray absorption variability has also been widely investigated in warm absorbers, BAL quasar winds, and ultra fast outflows (UFOs), usefully characterizing wind properties (e.g., Chartas et al 2009;Matt et al 2011;Saez et al 2012;King & Pounds 2015;Scott et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…X-ray photoelectric absorption variability has also been found in many Seyfert 2s (e.g., Risaliti et al 2002Risaliti et al , 2007. Modeling of the observed absorption variations suggests this absorption originates in gas clouds in the BLR or torus orbiting the central source (e.g., Maiolino et al 2010;Markowitz et al 2014;Torricelli-Ciamponi et al 2014;Netzer 2015). X-ray absorption variability has also been widely investigated in warm absorbers, BAL quasar winds, and ultra fast outflows (UFOs), usefully characterizing wind properties (e.g., Chartas et al 2009;Matt et al 2011;Saez et al 2012;King & Pounds 2015;Scott et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…sources changing from being absorbed by a Compton thin to a Compton thick column density). From the pioneering works of Risaliti et al (Risaliti et al 2002) on a few interesting sources such as the Seyfert 1 NGC 1365, to detailed studies on an increasing number of sources and on systematic studies of larger samples (Markowitz et al 2014;Torricelli-Ciamponi et al 2014;Tatum et al 2013), evidence has accumulated for the importance of large, complex, and variable neutral absorption also in type 1 Seyfert galaxies. Current interpretations for this cold circumnuclear gas are clumpy molecular tori (Krolik & Begelman 1988, Markowitz et al 2014Hönig 2013), absorption from inner and/or outer BLR clouds (Risaliti et al 2009), or accretion disc outflows (Elitzur & Shlosman 2006;Proga 2007;Sim et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of such variability must be significantly closer to the central region. Recently, Torricelli-Ciamponi et al (2014) have shown that X-ray eclipses are common when the expected occultation time is compatible with the exposure and that these events may be responsible for most of the spectral variability at energies higher than 2 keV. They associated the origin of the eclipsing clouds to the broad line region (BLR) of AGNs.…”
Section: Introductionmentioning
confidence: 99%